2005
DOI: 10.1007/s00264-005-0676-0
|View full text |Cite
|
Sign up to set email alerts
|

Retinacular band excision improves outcome in treatment of plica syndrome

Abstract: Mild symptoms usually continue after excision of the medial patellar plica. We noticed that the palpable tender cord, located on the anteromedial aspect of the knee in patients with plica syndrome, did not disappear completely after excision of the synovial fold. Beneath all plicae, a retinacular band was visible, and only after excisions of this band did the cord become impalpable. We conducted a study to determine the role of these medial retinacular bands in the symptomatology of the disorder. Twenty-four k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Patients resistant or unresponsive to conservative treatment may be treated surgically. Excellent results have been reported after the excision of symptomatic medial plicae [3,14,[16][17][18][19][20]. However, depending on the shape of the medial synovial plica and the duration of the impingement, cartilage damage may have already occurred or there may be concern about its future occurrence.…”
Section: Discussionmentioning
confidence: 88%
“…Patients resistant or unresponsive to conservative treatment may be treated surgically. Excellent results have been reported after the excision of symptomatic medial plicae [3,14,[16][17][18][19][20]. However, depending on the shape of the medial synovial plica and the duration of the impingement, cartilage damage may have already occurred or there may be concern about its future occurrence.…”
Section: Discussionmentioning
confidence: 88%
“… 37 The main rationale for this AMR was to eradicate the friction or impingement between the pathologic medial plica and the adjacent medial femoral condyle 32 34 by resecting the plica and releasing the fibrotic medial joint capsule and retinaculum. The beneficial effect of releasing retinaculum bands has also been verified and reported by Yilmaz et al 52 The effect of AMR was validated by a recent study 35 that investigated interleukin-1β (IL-1β) mRNA and matrix metalloproteinase-3 (MMP-3) mRNA expressions in the medial plica isolated from patients with different stages of medial compartment OA of the knee. According to this study, the repeated abrasions of the medial plica triggered IL-1β production and enhanced the expression of MMP-3.…”
Section: Discussionmentioning
confidence: 54%
“…Pekmezci et al described the case of a pathologic plica involving a check-valve mechanism [10]. Yilmaz et al reported that retinacular bands located beneath plicae on the anteromedial aspect of the knee in patients with plica syndrome played a role in the symptomatology and pathophysiology of plica syndrome and that their excision improved outcome [11]. In this case, similar band-like structures that resembled retinacular bands might have caused the anterior knee pain, as Yilmaz et al have remarked [11].…”
Section: Discussionmentioning
confidence: 80%
“…Yilmaz et al reported that retinacular bands located beneath plicae on the anteromedial aspect of the knee in patients with plica syndrome played a role in the symptomatology and pathophysiology of plica syndrome and that their excision improved outcome [11]. In this case, similar band-like structures that resembled retinacular bands might have caused the anterior knee pain, as Yilmaz et al have remarked [11]. Since the patient was presumably in her adolescent growth phase, joint growth may have resulted in tension on the remnant of the plica connected with the band-like structure in the suprapatellar pouch, which then intruded into the medial aspect of the patellofemoral joint and resulted in her symptoms.…”
Section: Discussionmentioning
confidence: 99%